Selecting an Individualized Treatment Approach: The Predictive Value of Erotic Stimulation and Nocturnal Erections for Efficacy of Tadalafil and Cure in Patients With Erectile Dysfunction - Liu, Zhiwei; Wu, Tao; Ma, Shanjin; Xue, Wei; Jiang, Xiaoye; Tang, Qisheng; Ma, Jianjun (Frontiers in Endocrinology, 2022)
Purpose: This study aimed to evaluate two modes of Rigiscan for predicting tadalafil response, and to identify which Rigiscan variables are the most efficient at making these predictions. Methods: All patients received at least two rounds of nocturnal penile tumescence and rigidity (NPTR) testing and/or audiovisual sexual stimulation (AVSS), then completed the International Index of Erectile Function-5 (IIEF-5) questionnaire, followed by oral 5 mg tadalafil daily for 4 weeks. After a 4-week washout period, all respondents underwent an the IIEF-5 questionnaire again. ED patients were then categorized into tadalafil responders and tadalafil non-responders, who were then further divided into cured patients and uncured patients. Results: When predicting tadalafil responders, the area under the curve (AUC) of NPTR was superior to that of AVSS (0.68~0.84 VS 0.69~0.73), and the predicted optimal cut-off values were DOEE60≥17.75 min in NPTR, compared to other parameters regardless of AVSS or NPTR (P<0.05). When predicting which patients would be cured, the AUC of AVSS was superior to NPTR parameters (0.77~0.81 vs 0.61~0.76), and the determined best diagnostic cut-off values were DOEE≥4.125min in AVSS, compared to other parameters regardless of AVSS or NPTR (P < 0.05). Conclusion: Rigiscan was able to predict the efficacy of daily tadalafil accurately and efficiently. Its diagnostic value was at maximum when DOEE60 ≥17.75 min of NPTR in tadalafil responders and DOEE ≥ 4.125 min of AVSS in cured patients.